Pengaruh Pemberian Teknik Marmet Terhadap Kelancaran Pengeluaran Produksi ASI Pada Ibu Post Partum Pada Klinik Kurnia Tahun 2022 - Nurul Aini Siagian; Jufenti Zega (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
The Effect of…Marmet…Technique…on Smooth Breastfeeding...in Post..Partum..Mothers..at the..Kurnia Clinic in 2022. Thesis, Midwifery Studies, Faculty of Midwifery. Breast..milk (ASI) is..a...white..liquid..produced..by..the..mother's..breast glands..through..the…breastfeeding…process. Breast..milk..is..food..that..has been..prepared..for..the..baby..when he is pregnant. Some of the obstacles that are often the reason for mothers to breastfeed are because of less milk production. One..of the..methods used..to overcome..the non-fluency..of breast..milk is..the marmet..technique. The..marmet technique..is a combination..of effective, manual, safe..and free..massage. The..marmet technique..is an..optimal..effort to..stimulate the hormones..oxytocin and prolactin..in the smooth..flow of breast milk. The purpose..of this study..was to determine the effect of the marmet technique on breastfeeding smoothness in postpartum mothers at the Kurnia clinic in 2022. It was a quasi-experimental study (quasi-experimental) with a one group pre and post design. The research population is post partum mothers as many as 20 people and..the number..of samples..is 10 respondents. Samples..were taken..using purposive..sampling. Hypothesis testing using..non-parametric using the Wilcoxon test. Obtained value 0.004 <0.05 then Ho is rejected Ha accepted. The results showed that the average result before the marmet technique was given was 1.50, while the average result after the marmet technique was 4.30, meaning..that..there was an effect of giving the marmet technique on breast..milk..production. Based..on..the..results of the research, it is hoped..that..the..research area will increase counseling and counseling about the effectiveness of breastfeeding..techniques using the marmet technique, so that the fulfillment of infant nutrition is fulfilled.